Evaluation of oral health related quality of life in patient with mild periodontitis among young male population of Namakkal district - Natarajan Shanmuga Sundaram; Ramesh Narendar; Palanisamy Dineshkumar; Sadasiva Balakrishnan Ramesh; Subramanium Gokulanathan (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of the study is to assess the impact of oral health related quality of life (QOL) on patients presenting for scaling and oral prophylaxis using a the oral health-related quality of life (OHRQL) questionnaire. Materials and Methods: This prospective study includes a total of 100 male patients of age group 25-35 years, who visited private clinic in Namakkal district, South India. They were assessed for their perceptions of oral health using OHRQL questionnaire before initial periodontal therapy including scaling and root planning. Results: A total of 100 patients (mean age:29 years) participated in the study and completed initial periodontal therapy. Before treatment 98% of the patients perceived that their oral health status impacted on their QOL in one or more ways. Bad breath was the most common complaint. Social well-being, personality and psychological function were identified as compromised OHRQL domains. More than 60% of the patients stated their overall general health is affected by periodontal disease. Conclusion: Periodontitis negatively affected QOL in this Namakkal district population of young male patients with mild periodontitis. Conventional non-surgical periodontal therapy and personality development counseling has a potential to ameliorate patient perceptions of oral health and improve their QOL.